Cultivation of tambaqui (Colossoma macropomum) in net tanks: Technical aspects (Research, Society and Development, 2021)
The tambaqui (Colossoma macropomum) is a native Amazonian species that presents good zootechnical performance in intensive rearing. The aim of this work was to verify the main aspects related to of C. macropomum cultivation in net cages, such as a suitable installation site, ease of handling, uses of feed and the physical, chemical and biological characteristics of the environment, relating to the potential and challenges of the cultivation of this species. For hatchling, a pocket-type nursery is necessary and subsequently pricking out to maintain the homogeneity of the size and weight of the fish. The breeding cycle lasts from 4 to 10 months, depending on the weight of the desired product, being divided into two phases: growing and fattening. The main factors that can enhance the growth of C. macropomum during the production cycle are stocking density, food and water quality appropriate, together with the adoption of good sanitary management practices and better control of disease prevention. The “curumim” tambaqui type is the main product sold from net tanks, it is commonly sold in natura, as fresh or frozen fish, has good carcass yield and is well accepted by the collective meals industries. Breeding presents economic risks, as the commercialized prices are close to the production cost. For the success of the activity, skilled labor, specialized technical assistance, rural extension to small producers are necessary to master the techniques of handling, planning and management of the activity.